The Comparison of Effectiveness of PjBL and PBL Models on Students’ Cognitive Learning Outcomes - Anik Suryani; Irma Setiawan; Syafruddin Muhdar; Fatmala Sari Oktaviani (STAI Hubbulwathan Duri, 2024)
In the autonomous curriculum, problem-based and PjBL paradigms are given priority. In terms of cognitive learning outcomes, this study aimed to evaluate the efficacy of PjBL and PBL models. This study employs a nonequivalent control group design and quantitative methodologies. Two groups are used in this study design: the control group employs the PBL model, while the experiment group uses the PjBL model. Forty fifth-grade children from a state elementary school in Cakranegara served as the study sample. A multiple-choice exam with 20 items was employed as the data gathering method. The experiment group's average score on the pre-test was 65.75 and their post-test was 81.25, while the control group's average score on the pre-test was 65.75 and their post-test was 75.50. The normality test revealed that the two groups' pre-test scores were identical, at 0.222, and their post-test scores were 0.109 and 0.063, respectively. These data analysis techniques include descriptive analysis tests. In order to achieve the findings of the precondition test of data testing using the SPSS 25 for Windows program, the homogeneity test was derived from the results based on a mean of 1.000. The data was homogenous and had a normal distribution, according to the findings. A significant value (2-tailed) of 0.0370.05 was shown by the data. In order to achieve the findings of the precondition test of data testing using the SPSS 25 for Windows program, the homogeneity test was derived from the results based on a mean of 1.000. The data was homogenous and had a normal distribution, according to the findings. A significant value (2-tailed) of 0.0370.05 was shown by the data. The experiment group and control group showed different cognitive learning results. Following treatment, the experiment group's average value was 81.25 whereas the control group's was 75.50. The experiment group (PjBL) is, therefore, more effective than the control group (PBL), it may be inferred. It has been demonstrated that utilizing both learning models enhances learning results.